Subjective Belief Distributions and the Characterization of Economic Literacy - Amalia Di Girolamo; Glenn Harrison; Morten Lau; J. Todd Swarthout (Institute for the Study of Labor (IZA), 2016)
We characterize the literacy of an individual in a domain by their elicited subjective belief distribution over the possible responses to a question posed in that domain. By eliciting the distribution, rather than just the answers to true/false or multiple choice questions, we can directly measure the confidence that an individual has about their knowledge of some fact. We consider literacy across several financial and economic domains. We find considerable demographic heterogeneity in the degree of literacy. We also measure the degree of consistency within a sample about their knowledge, even when that knowledge is imperfect.
Keywords: C91; D03; D83; 330; subjective beliefs; economic literacy